Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1467-8381.2009.02004.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Education in Cigarette Smoking: An Analysis of Malaysian Household Survey Data*

Abstract: Heckman's sample selection model is used to examine the role of education on household purchase decisions and expenditures of tobacco products in Malaysia. Results of the marginal effects of education, segmented by ethnic and gender groups, suggest that education decreases the probability, conditional levels and unconditional levels of tobacco expenditures amongst Malaysian households. Specifically, an additional year of education of the household head, irrespective of ethnic or gender considerations, decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 27 publications
9
27
2
Order By: Relevance
“…One, school connectedness-taken as the belief by students that teachers and lecturers cared about their learning, about them as individuals and the students had sense of attachment to their school (Morgan et al, 1991;Blum et al, 2004); the other -school adjustment referring to school related outcomes (Harakeh et al, 2005) and in this study taken as adolescents' perceived ability to cope with their school work compared to their peers. Numerous studies have found an inverse association between school factors and adolescent smoking behavior (Morgan et al, 1991;Tan et al, 2009). Even though our study showed only weak associations between both the school factors and smoking stages, the never smokers in our study had higher school connectedness and school adjustment scores compared to the rest of the smoking stages.…”
Section: Discussioncontrasting
confidence: 76%
“…One, school connectedness-taken as the belief by students that teachers and lecturers cared about their learning, about them as individuals and the students had sense of attachment to their school (Morgan et al, 1991;Blum et al, 2004); the other -school adjustment referring to school related outcomes (Harakeh et al, 2005) and in this study taken as adolescents' perceived ability to cope with their school work compared to their peers. Numerous studies have found an inverse association between school factors and adolescent smoking behavior (Morgan et al, 1991;Tan et al, 2009). Even though our study showed only weak associations between both the school factors and smoking stages, the never smokers in our study had higher school connectedness and school adjustment scores compared to the rest of the smoking stages.…”
Section: Discussioncontrasting
confidence: 76%
“…Better understanding of this topic may provide a clearer picture for the policy makers of the directions to design proper intervention strategies. To our knowledge, numerous studies have examined this issue in Malaysia (Siahpush et al, 2008;Lim et al, 2009;Tan et al, 2009;Al-Naggar and Saghir, 2011). However, they only focus on investigating the socio-demographic differences in smoking participation.…”
Section: Exploring Factors Influencing Smoking Behaviour In Malaysiamentioning
confidence: 99%
“…For instance, Tan et al (2009) use Malaysian Household Survey data and find that there are ethnic differences in households purchase decision of tobacco products. Similarly, Yen (2005) also observes that races may influence the propensity to smoke in US.…”
Section: Variablesmentioning
confidence: 99%
See 2 more Smart Citations